PENGARUH KERJASAMA DAN KREATIVITAS TERHADAP KINERJA PEGAWAI SATUAN POLISI PAMONG PRAJA KABUPATEN MUSI RAWAS - Gunadi Rusydi; Dheo Rimbano; Brori Hendrik (LPPM UNIVERSITAS BINA INSAN, 2021)
Broadly speaking and in general, the public only recognizes the functions of the Civil Service Police Unit of Musi Rawas Regency, which is limited to the scope of enforcing Regional Head Regulations, implementing Public Order, and Community protection units. However, the real essence of the description of the function and role of the Civil Service Police Unit of Musi Rawas Regency is to cover all activities in creating an atmosphere of public life that is orderly, clean, harmonious, and advanced. So, cooperation and group creativity are needed to achieve this, and this quantitative associative type research aims to prove it, by conducting a survey of 127 employees, the research results obtained: (1) Partially the Group Cooperation variable has a significant influence on the performance of the Regency Civil Service Police Unit. Rawas Musi; (2) Partially, the Creativity variable has a significant influence on the performance of the Civil Service Police Unit employees, Musi Rawas Regency; and (3) Simultaneously the independent variables (Group Cooperation and Creativity) have a significant effect on the dependent variable (employee performance).